Interactions between Tryptophan Metabolism, the Gut Microbiome and the Immune System as Potential Drivers of Non-Alcoholic Fatty Liver Disease (NAFLD) and Metabolic Diseases - Charlotte Teunis; Max Nieuwdorp; Nordin Hanssen (Metabolites, 2022)
The prevalence of non-alcoholic fatty liver disease (NAFLD) is increasing and therefore is its burden of disease as NALFD is a risk factor for cirrhosis and is associated with other metabolic conditions such as type II diabetes, obesity, dyslipidaemia and atherosclerosis. Linking these cardiometabolic diseases is a state of low-grade inflammation, with higher cytokines and c-reactive protein levels found in individuals with NAFLD, obesity and type II diabetes. A possible therapeutic target to decrease this state of low-grade inflammation is the metabolism of the essential amino-acid tryptophan. Its three main metabolic pathways (kynurenine pathway, indole pathway and serotonin/melatonin pathway) result in metabolites such as kynurenic acid, xanturenic acid, indole-3-propionic acid and serotonin/melatonin. The kynurenine pathway is regulated by indoleamine 2,3-dioxygenase (IDO), an enzyme that is upregulated by pro-inflammatory molecules such as INF, IL-6 and LPS. Higher activity of IDO is associated with increased inflammation and fibrosis in NAFLD, as well with increased glucose levels, obesity and atherosclerosis. On the other hand, increased concentrations of the indole pathway metabolites, regulated by the gut microbiome, seem to result in more favorable outcomes. This narrative review summarizes the interactions between tryptophan metabolism, the gut microbiome and the immune system as potential drivers of cardiometabolic diseases in NAFLD.